An Analysis of The English Textbook Entitled “Pathway to English” for Second Grade Students of Senior High School Based on Tomlinson’s Theory - Sholah, Hanif Maulaniam; Rohma, Cholifatur; pengelola, pengelola (Tasyri` : Jurnal Tarbiyah-Syari`ah-Islamiyah, 2021)
English is one of the most widely spoken international official languages worldwide. In Indonesia, English is used as a subject at various school levels. Teaching English itself is not an easy thing, so the role of media is very important in the learning process. One of the learning media that is often used and easy to find is textbooks. The purpose of this study was to determine the suitability of the textbook entitled Pathway to English with Tomlinson's theory. This research is a qualitative descriptive study with a focus on library research. The object of research is an English textbook entitled Pathway to English. The theory used to analyze is Tomlinson's theory. Data collection technique is obtained by in-depth observation of English textbooks. The technique of analyzing data is by reading, reducing data, presenting data, and verifying data. The results of this study indicate that the Pathway to English textbook meets the sixteen criteria contained in Tomlinson's theory. So that the textbook is declared fit for use as a learning medium. The author provides suggestions to several parties, including the teacher to pay more attention when choosing textbooks to be used during learning. To the publisher, it is suggested to publish quality books so that it can help the learning process to reaches the intended target.